Handbook of Research on Managing Information Systems in Developing Economies - Boateng, Richard (IGI Global, 2020)
Technology provides accessibility otherwise unavailable to the people who can benefit from it the most. As new digital tools become less expensive and more widely available, research and real-world cases that examine the union between emergent countries and information systems are essential in determining the next steps for these nations. The Handbook of Research on Managing Information Systems in Developing Economies is a pivotal reference source that explores the effects of technological data handling within developing economies. Covering a broad range of topics such as emerging digital tech.